Toxoplasma gondii Arginine Methyltransferase 1 (PRMT1) Is Necessary for Centrosome Dynamics during Tachyzoite Cell Division - El Bissati, Kamal (mBio, 2016)
The arginine methyltransferase family (PRMT) has been implicated in a variety of cellular processes, including signal transduction, epigenetic regulation, and DNA repair pathways. PRMT1 is thought to be responsible for the majority of PRMT activity in Toxoplasma gondii, but its exact function is unknown. To further define the biological function of the PRMT family, we generated T. gondii mutants lacking PRMT1 (Δprmt1) by deletion of the PRMT1 gene. Δprmt1 parasites exhibit morphological defects during cell division and grow slowly, and this phenotype reverses in the Δprmt::PRMT1mRFP complemented strain. Tagged PRMT1 localizes primarily in the cytoplasm with enrichment at the pericentriolar material, and the strain lacking PRMT1 is unable to segregate progeny accurately. Unlike wild-type and complemented parasites, Δprmt1 parasites have abnormal daughter buds, perturbed centrosome stoichiometry, and loss of synchronous replication. Whole-genome expression profiling demonstrated differences in expression of cell-cycle-regulated genes in the Δprmt1 strain relative to the complemented Δprmt1::PRMT1mRFP and parental wild-type strains, but these changes do not correlate with a specific block in cell cycle. Although PRMT1’s primary biological function was previously proposed to be methylation of histones, our studies suggest that PRMT1 plays an important role within the centrosome to ensure the proper replication of the parasite.